The Role of Precedents and Suffixes in the Temporal Structure of Narrative: The Novel "Ikhtia" as a Model - Ghada Mohammed Ebrahim (Ijaz Arabi Journal of Arabic Learning, 2023)
This study examines the role of precedents and suffixes in narrative temporal structure, identifying Gent's sorts of precedents and suffixes and locating them in Emile Habibi's novel "Ikhtia" and their purposes in the story's chronology. This study used a descriptive and inductive approach to track temporal growth between antecedents and suffixes, describing the temporal phenomena and extrapolating the sorts of narrative temporal movements in "Ikhtia." The study found that the novel "Ikhtia timeline" of events revealed clues about the logical temporal hierarchy and that this fragmentation of events helped the narrator rewrite the story. Because "Ikhtia" is a self-narrated novel, the narrator knows all the events and people. "Ikhtia" used foresight through internal precedents that marry the basic tale and the anticipatory tale, resulting in the repetition of important events and the narrator's anticipation of future visions, arousing the reader's interest, as well as external precedents that push the events to a logical end, whether it is the frequency type, which always completes the tale, or the repetition type, which performs the same function. Based on the analytical study of the temporal structure of the novel "Ikhtia," the research concluded with several main recommendations, the most important of which is the need to pay attention to the practical aspects of critical theories to reveal their effectiveness in studying texts, diversify the tools for analyzing literary texts to come up with richer and deeper results in understanding them, and attempt to master the latent energies of the lit.